Perlindungan Hukum Terhadap Nasabah Bank Korban Kejahatan Skimming - Juita, Subaidah Ratna; Astanti, Dhian Indah; Septiandani, Dian (Universitas Semarang, 2023)
Theft of bank customer money through the mode of duplicating ATM cards (skimming) is one of the banking crimes. This paper is the result of research focusing on the study of legal protection for bank customers due to skimming crimes. This research was conducted with a normative juridical approach using data collection methods through literature studies conducted on secondary data. Secondary data is obtained through various laws and regulations, books, internet media, and scientific journals in order to obtain results of studies regarding the crime of ATM card skimming and legal protection for bank customers who are harmed by skimming crimes. Furthermore, the data analysis method uses descriptive analysis. Meanwhile, the urgency of this research is expected to be a source of reference for banking institutions to carry out legal protection efforts as well as for law enforcement officials in carrying out efforts to combat skimming crimes as a concrete form of legal protection for bank customers who are harmed by skimming crimes.Thus, the juridical-normative approach in this study is used to analyze issues related to legal protection of bank customers due to skimming crimes. Based on the analysis, it was identified that the crime of stealing customer money using the skimming method is one of the crimes with a high-tech dimension (cyber crime) in the banking sector. This action is included in the criminal act of information and electronic transactions which prohibits everyone intentionally and without rights or unlawfully accessing computers and or electronic systems in any way with the aim of obtaining electronic information and or electronic documents as stipulated in Article 30 paragraph (2) Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE Law). Protection of customers who are victims of skimming crimes can be carried out in the context of criminal law enforcement and civil law enforcement. Pencurian uang nasabah bank melalui modus penggandaan kartu ATM (skimming) merupakan salah satu kejahatan perbankan. Tulisan ini merupakan hasil penelitian dengan memfokuskan pada kajian mengenai perlindungan hukum terhadap nasabah bank akibat kejahatan skimming. Penelitian ini dilakukan dengan pendekatan yuridis normatif dengan menggunakan metode pengumpulan data melalui studi pustaka yang dilakukan terhadap data sekunder. Selanjutnya metode analisis data menggunakan analisis deskriptif analitis. Sementara itu urgensi penelitian ini diharapkan dapat menjadi sumber rujukan bagi lembaga perbankan untuk melakukan upaya perlindungan hukum sekaligus bagi aparat penegak hukum dalam melakukan upaya penanggulangan kejahatan skimming sebagai wujud konkret perlindungan hukum terhadap nasabah bank yang dirugikan akibat kejahatan skimming, Berdasarkan analisis, diidentifikasikan bahwa kejahatan pembobolan uang nasabah dengan metode skimming merupakan salah satu kejahatan berdimensi high-tech (cyber crime) di bidang perbankan. Perbuatan tersebut termasuk dalam tindak pidana informasi dan transaksi elektronik yang melarang setiap orang dengan sengaja dan tanpa hak atau melawan hukum mengakses komputer dan atau sistem elektronik dengan cara apapun dengan tujuan untuk memperoleh informasi elektronik dan atau dokumen elektronik sebagaimana diatur dalam Pasal 30 ayat (2) Undang-Undang Nomor 19 Tahun 2016 tentang Perubahan atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik (Undang-Undang ITE). Perlindungan terhadap nasabah korban kejahatan skimming dapat dilakukan dalam konteks penegakan hukum pidana dan penegakan hukum perdata. Kejahatan Skimming; Nasabah Bank; Perlindungan Hukum